Implementation of Realistic Mathematics Education in Indonesia - Febrilia, Yeyen; Saputra, Julianto; Purnasari, Pebria Dheni; Helisman, Helisman (Universitas Ahmad Dahlan, 2025)
This research explores how Realistic Mathematics Education (RME) has been applied within the Indonesian context. Employing a Systematic Literature Review (SLR) approach, the study involves identifying, examining, critically evaluating, and interpreting scholarly articles from multiple perspectives. The data set comprises 15 peer-reviewed international publications from the Scopus database through the Publish or Perish tool, covering 2005 to 2022. These articles originate from various countries, including Indonesia, the Netherlands, Vietnam, Turkey, Greece, Norway, the United States, and Italy. The study examines the application of RME across different nations, focusing on Indonesia, and identifies the key elements that facilitate its implementation. Findings indicate that the integration of RME in Indonesia contributes to improving students’ conceptual understanding.